Photoexcitation in Solids: First‐Principles Quantum Simulations by Real‐Time TDDFT. Issue 8 (1st July 2018) - Lian, Chao; Guan, Mengxue; Hu, Shiqi; Zhang, Jin; Meng, Sheng
Abstract: An efficient and state‐of‐the‐art real‐time time‐dependent density functional theory (rt‐TDDFT) method is presented, as implemented in the time‐dependent ab initio package (TDAP), which aims at performing accurate simulations of the interaction between laser fields and solid‐state materials. The combination of length‐gauge and velocity‐gauge electromagnetic field has extended the diversity of materials under consideration, ranging from low dimensional systems to periodic solids. Meanwhile, by employing a local basis presentation, systems of a large size are simulated for long electronic propagation time, with moderate computational cost while maintaining a relatively high accuracy. Non‐perturbative phenomena in materials under a strong laser field and linear responses in a weak field can be simulated, either in the presence of ionic motions or not. Several quintessential works are introduced as examples for applications of this approach, including photoabsorption properties of armchair graphene nanoribbon, hole‐transfer ultrafast dynamics between MoS2 /WS2 interlayer heterojunction, laser‐induced nonthermal melting of silicon, and high harmonic generation in monolayer MoS2 . The method demonstrates great potential for studying ultrafast electron‐nuclear dynamics and nonequilibrium phenomena in a wide range of quantum systems. Abstract : Solid‐state materials can exhibit highly nonlinear electronic and optical behaviors under laser excitation. However, a unified theoretical framework has not been established to explain the underlying mechanisms. Here, an efficient real‐time time‐dependent density functional theory approach is developed for accurate simulations of excited state dynamics in solids. Detailed flow and implementation of this method are discussed. Meanwhile, several quintessential examples for applications are introduced. .